2010
DOI: 10.1038/cdd.2010.57
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor Sox2 is required for osteoblast self-renewal

Abstract: The development and maintenance of most tissues and organs requires the presence of multipotent and unipotent stem cells that have the ability of self-renewal as well as of generating committed, further differentiated cell types. The transcription factor Sox2 is essential for embryonic development and maintains pluripotency and self-renewal in embryonic stem cells. It is expressed in immature osteoblasts/osteoprogenitors in vitro and in vivo and is induced by FGF signaling, which stimulates osteoblast prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(94 citation statements)
references
References 43 publications
6
88
0
Order By: Relevance
“…Recently, a novel function for Sox2 was identified in a mouse osteoblastic lineage: the maintenance of the self-renewal of cells. In addition, Sox2-knockout cells could not form colonies, and their population growth was arrested with a senescent phenotype (Basu-Roy et al, 2010). In another study, most Sox2-overexpressed BMSCs were small and showed high proliferative and osteogenic capabilities from human BMSCs (Go et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a novel function for Sox2 was identified in a mouse osteoblastic lineage: the maintenance of the self-renewal of cells. In addition, Sox2-knockout cells could not form colonies, and their population growth was arrested with a senescent phenotype (Basu-Roy et al, 2010). In another study, most Sox2-overexpressed BMSCs were small and showed high proliferative and osteogenic capabilities from human BMSCs (Go et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The Sox2 transcription factor is crucial for the maintenance of several types of stem cells, including pluripotent, neural and osteogenic stem cells (Masui et al, 2007;Favaro et al, 2009;Basu Roy et al, 2010). Despite the importance of Sox2 in NSCs in vitro, major abnormalities in brain development were not detected by conditional ablation of Sox2 at midgestation (E12.5) in mouse, with the exception of defects in postnatal development of the hippocampus dentate gyrus and of the retina (Taranova et al, 2006;Miyagi et al, 2008;Favaro et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Later in development, Sox2 is required in various tissue stem cells and early progenitors, in particular in the nervous system (Que et al, 2009;Basu-Roy et al, 2010;Pevny and Nicolis, 2010). Throughout vertebrate evolution, Sox2 is expressed in the developing neuroectoderm from its earliest stages (Wegner and Stolt, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The transcription factor Sox2, a member of the SY-related, HMG box family, plays a critical role in embryonic development and maintenance of pluripotency and self-renewal of embryonic stem cells [29,30]. Furthermore, Sox2 is also involved in the maintenance of self-renewal of the osteoblastic lineage [31]. Recently, it was shown that mesenchymal stem cells derived from human umbilical cord constitutively express SOX2 and are capable of differentiating into osteoblast as well as adipocytes, indicating the involvement of SOX2 in osteoblast differentiation [32].…”
Section: Discussionmentioning
confidence: 99%